PENGEMBANGAN LEMBAR KEGIATAN SISWA (LKS) BERBASIS LEARNING CYCLE 5E UNTUK MENINGKATKAN PEMAHAMAN KONSEP SISWA - Kaka, Ester Willu; Hunaepi, Hunaepi; Masiah, Masiah (Bioscientist : Jurnal Ilmiah Biologi, 2016)
<!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]--><span style="font-size: 10.0pt; font-family: 'Times New Roman','serif'; mso-fareast-font-family: 'Times New Roman'; letter-spacing: -.05pt; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">ABSTRACT:<span style="font-size: 10.0pt; font-family: 'Times New Roman','serif'; mso-fareast-font-family: 'Times New Roman'; letter-spacing: .1pt; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">T<span style="font-size: 10.0pt; font-family: 'Times New Roman','serif'; mso-fareast-font-family: 'Times New Roman'; letter-spacing: -.1pt; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">heaimsofthisresearchistodeveloping studentworksheetofintegratednatureofscience based of5elearning cycle modelto improvestudentconceptualunderstanding. TheMastery of the conceptcanbedefinedas theability ofstudentsto understandthemeaning ofscientific,that is understanding ofconcepttheoretically anditsapplication ineveryday life. This researchcountedin reseaechand development (R&D),andthemodel referenced indeveloping thisstudentworksheetof integrated natureof science isADDIEModel (Analysis, Design,Development,Implementation, Evaluation).Thedevelopmentofthisstudentworksheetofintegratednatureofscienceisonlyuntil thestageofdevelopmentalone.Aspectsofstudentworksheetofintegratednatureodsciencethat is developedinthisresearch includeaspectsoffeasibility,practicality,andeffectiveness.Basedonthe results of the research to test the feasibility, practicality, effectivenessand students'response to student worksheetof integratednatureofscience, canbeconcluded: the validity of the developmentisdone to determinethefeasibility ofstudentworksheetofintegratednatureofsciencebasedlearning cycle5e refers to the resultsof theassessmentitcanbeconcluded thatstudentworksheethavevery decent categorywithapercentageoftheaverageoflecturejudgmentis76.78%,andpercentagefrom thethe teacher judgmentis79,31%.Practicality ofstudent workheetwereassessedby two(2)teacherof integratednatureofscience,thatstudentworksheetisverypracticalcategorywith94,8%.Theresults oftrialson theeffectivenessofstudentworksheets totaling 34students, thatthe studentworksheetis categorizedquiteeffectively withapercentageof79.55%andtheresultsoftheanalysisteststudents' responsesarerepresentedby10students,LKScategorizedasveryfeasiblewithapercentageof 76.66%, thus thedevelopedstudentworksheetbased learning cycle5efeasibletobeusedto improve studentconceptualunderstanding.<!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]-->